Hervey Cleckley: A Man ahead of Time - Antsyborov A. V., Dubatova I. V. (Interactive science, 2019)
hervey Cleckley is one of the most influential psychiatrists of the 20th century. Part of his scientific research still causes debates in the scientific world, especially his works about «successful psychopaths» and the curability of psychopathy. Most of Cleckley’s scientific works in the field of the study of psychopathy are well known to most modern scholars, and some of his articles have become textbooks. At the same time, his works on dissociative personality are less known in the professional community. Through the time, his scientific achievements have not lost their relevance and scientific novelty.
Keywords: биография; история медицины; biography; психопатия; антисоциальное расстройство личности; psychopathy; antisocial personality disorder; history of medicine